Metallic Dendrites: How Far Can We Go? - Kumari R.; Shubhangi; Dkhar D.S.; Chandra P. (My University, 2025)
Metallic dendrites, novel hierarchical nanostructures with a distinctive fern- or tree-like appearance, introduce a new era in sensing and wearable technologies. They possess several properties, including high surface area, crystal defects, grain boundaries, and edge sites, all of which contribute to an increased number of catalytic sites for sensing and wearable platforms, as well as functionalization sites for antibodies and drug molecules’ adhesion. The aforementioned characteristics endow them with superior conductivity and enhanced catalytic activity, thereby facilitating improved mass and charge transfer rates of analytes in catalytic platforms. Since their discovery, there has been substantial progress in their synthesis, nanoengineering with composites, and extensive analytical applications in diverse domains, such as sensor platforms and wearables, fuel cells, supercapacitors, and drug delivery. Although platforms based on dendrites have performed well over the past ten years, their commercialization has yet to take place for a variety of reasons, primarily being the challenge to achieve homogeneity in large-scale synthesis due to uncontrolled development. Besides this, other challenges include transitioning to non-noble metals while still maintaining high activity and stability, as well as their sluggish metabolism in vivo following drug delivery and poor excretion by the body, which collectively hinder their translation. This Perspective encompasses important breakthroughs of metallic dendrites and analytical platforms based upon them, crucial knowledge gaps, and bottlenecks in commercialization with an eye towards the future of dendrite-based sensing, wearable electronics, as well as other such platforms. © 2025 American Chemical Society.